2022
DOI: 10.4103/njcp.njcp_2006_21
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Electronic Cigarette Usage Among Medical Students in Saudi Arabia – A Systematic Review

Abstract: The systematic review aimed to report the prevalence of electronic cigarette (e-cigarette) usage among medical students in Saudi Arabia. Electronic databases were searched for scientific research articles published from January 2010 until December 2020. The data search was performed in electronic search engines such as PubMed, Google Scholar, Scopus, Web of Science, Medline, Embase, Cochrane, and Saudi Digital Library. A total of five research articles that qualified the eligibility criteria were analyzed for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Moreover, the data reveal that 60.9% of them began smoking before the age of eighteen years old, and 29.7% of them did so before the age of fifteen years old [ 60 ]. In Saudi Arabia, the percentage of medical students who used e-cigarettes ranged from 10.6% to 27.7% [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the data reveal that 60.9% of them began smoking before the age of eighteen years old, and 29.7% of them did so before the age of fifteen years old [ 60 ]. In Saudi Arabia, the percentage of medical students who used e-cigarettes ranged from 10.6% to 27.7% [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Althobaiti N.K et al [ 27 ] found that young adults from the Mecca Region of Saudi Arabia, aged 18 to 24 years old, had a prevalence of 26%. According to a systematic review by Patil S et al [ 28 ], between 10.6% and 27.7% of Saudi Arabian medical students used e-cigarettes. According to Sharanesha RB et al [ 29 ], dental students in the Riyadh region of Saudi Arabia use e-cigarettes at a rate of 21%.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that younger adults are more likely to use e-cigarettes than older adults. Many studies have been done on the Saudi Arabian population regarding e-cigarette usage, concluding that youth are more likely to use e-cigarettes (Patil et al, 2022). E-cigarettes have gained popularity over the past few years, especially among young people.…”
mentioning
confidence: 99%